دور التقدم التقني في تطور صناعة السياحة الإماراتية مع الإشارة إلى حالة الجزائر: قراءة إحصائية في الفترة 1995-2019 - سلامي، أسماء; سلامي، أحمد بوبكر (جامعة الشهيد حمه لخضر الوادي - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2021)
تهدف الدراسة إلى إبراز دور التقدم التقني في تطوير صناعة السياحة الإماراتية بدولة الإمارات، من منطلق أن تجربة هذه الأخيرة تعد من أهم التجارب الناجحة في هذا المجال، ولهذا الغرض استخدمنا المنهج الوصفي التحليلي. النتائج تشير إلى أن الإمارات أضحت تتمتع ببنية سياحية متطورة، واستطاعت ابتكار وسائل جذب غير مسبوقة شجعت السياح على ارتيادها، وصارت وجهة سياحية مفضلة لكل سكان العالم، لتحل في المركز الأول عربيا والــــــ 33 عالميا ضمن قائمة الدول الأكثر تطورا في قطاع السفر والسياحة من أصل 140 دولة شملها تقرير 2019. وقد تحقق لها ذلك نتيجة تمكنها من إتاحة بنى تحتية متطورة جدا في صناعة المعلومات والتكنولوجيا الخاصة بالاتصالات كأحد عوامل الجذب السياحي، ما أدى إلى ارتفاع معتبر في قيمة عوائدها السياحية التي وصلت إلى 21,39مليار $ سنة 2018، بعدما كانت لا تتجاوز 632 مليو ن $ سنة 1995. كما ارتفع عدد سياحها عام 2018 إلى 21,28 مليون سائح. لكن بالنسبة للسياحة الجزائرية فلا زالت متخلفة، وخاصة محدودية التكنولوجيا المستخدمة فيها، وهامشية الجهد في البحث والتطوير، ويعود هذا إلى عدم الاهتمام بالمتغير التكنولوجي كمقوم أساسي في تنشيط الطلب على الخدمات السياحية. لذا توصي الدراسة بضرورة أن تستفيد الجزائر من التجربة الناجحة للإمارات في تطبيق المعلوماتية، وذلك بوضع خطة شاملة لتطوير وتحديث البنية التحتية لتكنولوجيا المعلومات والاتصالات.
The study aims to showings the role of technical progress in developing of the UAE tourism industry, on the grounds that the experience of the latter is considered one of the most successful experiences in this field, and for this purpose we used the descriptive analytical approach. The results indicate that the UAE has become a developed tourism infrastructure, and has been able to devise unprecedented attractions that encouraged tourists to visit it, and it has become a favorite tourist destination for all of the world's population, to be ranked first in the Arab world and 33 globally among the list of most developed countries in the travel and tourism sector out of 140 A country included in the 2019 report. This was achieved as a result of its ability to provide very advanced infrastructure in the information and communications technology industry as one of the factors of tourism attraction, which led to a significant increase in the value of its tourism revenues, which reached $ 21.39 billion in 2018, after it was not more than $ 632 million in the year 1995. As number of its tourists in 2018 to 21.28 million tourists. But as for Algerian tourism, it is still underdeveloped, especially the limited technology used in it, and the marginal effort in research and development, due to the lack of interest in the technological variable as a basic basis in stimulating the demand for tourism services. Therefore, the study recommends that Algeria should benefit from the successful experience of the Emirates in the application of informatics, by setting a comprehensive plan to develop and modernize the infrastructure of information and communication technology.
Keywords: التقنيات الحديثة -- السياحة الإماراتية -- الاقتصاد الجزائري -- السياحة الإلكترونية